The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.23954/osj.v2i4.1219
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Sustainability and the Circular Economy as Counterparts to the Self-Referral Structure of Natural Law: Part II – A Global Case Study

Abstract: Part I of this two-part series of research papers identified the theoretical foundations of industrial sustainability and circular economy in the structure of Natural Law, as explained by Maharishi Vedic Science. Part I showed that all levels of a manifest hierarchy are governed by self-referral and selfinteracting feedback loops, and maintained that the circular economic model represents a counterpart to the self-referral mechanics of Natural Law and is therefore more in accord with Natural Law than the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…297-300]). Such is the case for one of the world's most hazardous industrial solid waste streams [e.g., 59] which, when re-conceived as part of CE involving information exchanges and cooperative industrial handshaking as shown in Part II of this research series [28], can be transformed from being a threat to society to being reconnected to the wholeness of Natural Law through the selfreferral mechanics described in this paper. In these ways, all industrial wastes, including hazardous wastes, have the potential to be aligned with Natural Law and harness its selfreferral mechanics, thereby creating balance rather than disease throughout society.…”
Section: Fig 7 Relationship Between Materials Inputs Industrial Thmentioning
confidence: 99%
See 1 more Smart Citation
“…297-300]). Such is the case for one of the world's most hazardous industrial solid waste streams [e.g., 59] which, when re-conceived as part of CE involving information exchanges and cooperative industrial handshaking as shown in Part II of this research series [28], can be transformed from being a threat to society to being reconnected to the wholeness of Natural Law through the selfreferral mechanics described in this paper. In these ways, all industrial wastes, including hazardous wastes, have the potential to be aligned with Natural Law and harness its selfreferral mechanics, thereby creating balance rather than disease throughout society.…”
Section: Fig 7 Relationship Between Materials Inputs Industrial Thmentioning
confidence: 99%
“…The paper is organised into three sections beyond this Introduction: the first examines the self-referral nature and structural levels of Natural Law as elucidated by Maharishi Vedic Science; the second considers the circularity of industrial sustainability and CE; and the third explores how the basic principles of industrial sustainability and CE mimic or closely resemble the self-referral mechanics of nature, and can thus be considered "counterparts" to Natural Law. Part II, which follows as a separate research study, presents alumina refinery residue, one of the world's largest and most problematic hazardous wastes, as an example of self-referral industrial processing and partnering in the context of sustainability and CE [28].…”
Section: Introductionmentioning
confidence: 99%